Ojcostwo w świecie współczesnym - Anna Więcławska (Nicolaus Copernicus University in Toruń, 2009)
In present times we are witnessing the crisis of fatherhood. This crisis stems not only from the behaviour of men themselves but it is largely connected with the questioning of the role of the husband and father which men should have as well as the crisis of marriage and family which are the fundamental principles of mature and responsible fatherhood. In the culture today most men follow to some degree the model of a passive, uninvolved and absent father. This absence must finally end. Our society, which has been brought up without fathers, must finally accept the value of fatherhood. The end of patriarchy has become the beginning of a new fatherhood epoch, a new paradigm of masculinity. This paradigm focuses on the equality and partnership of men and women, accepting these values as fundamental in creating a new social order. It includes the concept of self-fulfillment and androgyny meant as aiming at complete humanity. Saving the family is possible only by the revival of fatherhood - the return to the model or creating a new human and new men-women relations which give happiness. A human is created through upbringing and self-upbringing. Therefore to be the father one must be brought up to this role.